Palladium Phthalocyanines Varying in Substituents Position for Photodynamic Inactivation of Flavobacterium hydatis as Sensitive and Resistant Species - Vanya Mantareva; Vesselin Kussovski; Petya Orozova; Ivan Angelov; Mahmut Durmuş; Hristo Najdenski (Current Issues in Molecular Biology, 2022)
Antimicrobial photodynamic therapy (aPDT) has been considered as a promising methodology to fight the multidrug resistance of pathogenic bacteria. The procedure involves a photoactive compound (photosensitizer), the red or near infrared spectrum for its activation, and an oxygen environment. In general, reactive oxygen species are toxic to biomolecules which feature a mechanism of photodynamic action. The present study evaluates two clinical isolates of Gram-negative Flavobacteriumhydatis (F. hydatis): a multidrug resistant (R) and a sensitive (S) strain. Both occur in farmed fish, leading to the big production losses because of the inefficacy of antibiotics. Palladium phthalocyanines (PdPcs) with methylpyridiloxy groups linked peripherally (pPdPc) or non-peripherally (nPdPc) were studied with full photodynamic inactivation for 5.0 µM nPdPc toward both F. hydatis, R and S strains (6 log), but with a half of this value (3 log) for 5.0 µM pPdPc and only for F. hydatis, S. In addition to the newly synthesized PdPcs as a “positive control” was applied a well-known highly effective zinc phthalocyanine (ZnPcMe). ZnPcMe showed optimal photocytotoxicity for inactivation of both F. hydatis R and S. The present study is encouraging for a further development of aPDT with phthalocyanines as an alternative method to antibiotic medication to keep under control the harmful pathogens in aquacultures’ farms.